The multifaceted nature of Egyptian mummification: Paleoradiological insights into child mummies. - Stephanie Zesch; Stephanie Panzer; Alice Paladin; M Linda Sutherland; Susanne Lindauer; Ronny Friedrich; Tanja Pommerening; Albert Zink; Wilfried Rosendahl (PLoS ONE)
In accordance with ancient Egyptian beliefs, the preservation of the body after death was an important prerequisite for the continued existence of the deceased in the afterlife. This involved application of various physical interventions and magical rituals to the corpse. Computed tomography (CT), as the gold-standard technology in the field of paleoradiology, enables deeper insights into details of artificial body preservation. Therefore, CT was applied to investigate age at death, sex, mummification techniques, and the state of soft tissue preservation in 21 child mummies. The specimens are housed in European museums and were found in various archaeological sites. This sample included 12 males, 7 females, and two specimens of unknown sex, all between the ages of one and 14 years. Time periods were determined by radiocarbon dating, and time-related indicators of funerary equipment and decoration. Most of the mummies date from the Late Period to the Roman Period (664 BC-395 AD). Differences were identified concerning techniques of wrapping and embalming and removal of brain and internal organs, depending on age at death, social status and the archaeological site of the individuals. The variety and multifaceted nature of mummification and soft tissue preservation was analyzed in an integrated approach including a large number of specimens. The study highlights the significance of subadult remains as valuable bioarcheological archives to investigate burial customs and religious concepts in past societies.